ANALISIS RESIKO USAHATANI TEMBAKAU DI DESA WAY WANGI KECAMATAN WARKUK RANAU SELATAN KABUPATEN OGAN KOMERING ULU SELATAN (JASEP, 2019)
This research was coducted in Way Wangi Village, South Warkuk Ranau Subdistrict, South Ogan Komering Ulu Regency, where the determination of the area was done purposively. Because Based on data obtained from the agriculture and plantation Office of South Ogan Komering Ulu Regency, that tabacco farming in Way Wangi Vilagge is highest in production compared to other villages. Implementation of research conducted in October 2017 until November 2017. The method used in this research is survey method. Procesed and analyzed at the same time income and income risk. The result showed that tabacco farming in Way Wangi Village, South Warkuk Ranau Subdistrict, South Ogan Komering Ulu Regency, resulted in average income of Rp. 54.367.880. from these calculations it can be seen the amount of standard deviation of Rp.15.718.548,16657. The coefficient of variation obtained is 0.2891146053 which means the CV is less than 0.5 (0.28 ≤ 0.5) and L more than (22.930.783.666859 ≥ 0). This indicates that tabacco farming in Way Wangi village, South Warkuk Ranau Subdistrict, South Ogan Komering Ulu Regency is protected from loss.